Valuation With Real Opions and Games - alyanak, tunc (2007)
Strategic considerations concerning real options analysis were mostly focused on imperfect competition and specifically on duopoly models. In this perspective, the issues of first-mover advantages and the investment cost under uncertainty conditions were of intense concern. Moreover, although in the context of real options and competition topics such as research and development, real-estate investments, acquisitions and foreign direct investments were treated by various authors, the case of company valuation with compound real options and games has attracted less interest. In this perspective, through this research our main goal was to develop a company valuation framework which takes into account the case of a company faced with a compound real option in the context of an oligopolistic market structure. To analyse the value of a company, throughout this dissertation a hypothetical model has been formed based on a real-world case.